Analisa Penerapan Supply Chain Management pada PT. Pertamina (Persero) - , Intan Hertikasari Susilo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Control of the Supply Chain Management effectively and efficiently is a key to the success of a company to survive in the tight industry competition. Point in Supply Chain is how to optimize the companyâs resources (raw materials, processes, technology, capability, capital) in the existing economic and business environment in order to achieve the company's competitiveness and to gain maximum profit by maintaining high sustainability. This study aimed to analyze the implementation of Supply Chain Management, identifies the supporting factors and inhibiting factors, provide efforts which can be taken to optimize the implementation of Supply Chain Management at PT. Pertamina (Persero). The effectiveness of the implementation of Supply Chain Management are analyzed based on the achievement of Key Performance Indicator (KPI), in-depth individual interviews (IDI) and the study of best practice with Multinational Oil Company. The results showed that the implementation of Supply Chain Management at PT. Pertamina (Persero) is not optimal in the production, hoarding, distribution and sale of fuel and LPG. Supporting Factors are already done marketing optimization and processing (refinery), interaction trading/ procurement to the market through a single door (single interface) by ISC and conducted joint planning ranging from processing, supply, marketing, and distribution. While the inhibiting factors are the supply chain management of PT Pertamina (Persero) is not integrated as a whole, the condition of facilities and infrastructure does not support, master scheduling program frequently change, Pertamina gas station service standards below competitors, uneven quality of human resources and mutual cooperation among producers in southeast Asian and surrounding are not maximum. Efforts should be made to optimize the implementation of SCM are by integrating all components of the supply chain of PT Pertamina (Persero) such as suppliers, manufacturers, warehouses and stores into a single system, optimization of facilities and infrastructure, integrating the entire downstream, implement New Pasti Pas concepts, improving the quality of human resources and increased mutually beneficial cooperation with other manufacturers in the southeast Asian region and surrounding area.